Kecenderungan Kecemasan Neurotik Willy Wonka dalam Novel Charlie and The Chocolate Factory Karya Roald Dahl - Anang Viki Pratama Hadju (Balai Bahasa Provinsi Riau, 2018)
This study uses psychoanalysis concept, there is a tendency of neurotic anxiety in the main characters in Charlie and The Chocolate Factory, a novel by Roald Dahl. This study finds the character’s personality, Willy Wonka as main character becomes neurotic anxiety who influenced by the three systems of personality, they are Id, Ego, and Superego. The purpose of this study is to determine what aspects that make Willy Wonka has neurotic anxiety and his effort to relieve it. The result of this study is Willy Wonka feels anxiety, nervous and panic as a result of traumatic experience before. So, Willy Wonka deliberately makes a competition as form of reason for his self-defense mechanism to think of finding the best way to reduce his anxiety for a while. This study is expected to contribute to the understanding of the human mind and significance object between literature and the psychological condition.